Psychosocial job stressors and thoughts about suicide among males: a cross-sectional study from the first wave of the Ten to Men cohort. (June 2017) - Milner, A.; Currier, D.; LaMontagne, A.D.; Spittal, M.J.; Pirkis, J.
Abstract: Objectives: Psychosocial job stressors are known to be associated with poor mental health. This research seeks to assess the relationship between psychosocial working conditions and suicidal ideation using a large dataset of Australian males. Study design: Cross-sectional study. Methods: Data from wave 1 of the Australian Longitudinal Study on Male Health (Ten to Men) was used to assess the association between suicidal ideation in the past two weeks and psychosocial working conditions using logistic regression. The sample included 11, 052 working males. The exposures included self-reported low job control, high job demands, job insecurity and low fairness of pay. We controlled for relevant confounders. Results: In multivariable analysis, persons who were exposed to low job control (odds ratio [OR] 1.15, 95% confidence interval [CI] 1.05–1.26, P  = 0.003), job insecurity (OR 1.69, 95% CI 1.44–1.99, P  < 0.001) and unfair pay (OR 1.19, 95% CI 1.11–1.27, P  < 0.001) reported elevated odds of thoughts about suicide. Males employed casually or on fixed-term contracts reported higher odds of suicidal ideation (OR 1.32, 95% CI 1.09–1.61, P  = 0.005). Conclusion: Psychosocial job stressors are highly prevalent in the working population and workplace suicide prevention efforts should aim to address these as possible risk factors. Highlights: Psychosocial job stressors are associated with a large range of health outcomes. There is a lack of research on job stressors and male suicidal ideation. Low job control, high demands and job insecurity were risk factors. Workplace suicide prevention needs to address adverse working conditions.